Preclinical insights into the gut‐skeletal muscle axis in chronic gastrointestinal diseases. Issue 15 (6th July 2020) - Ehlers, Luise; Bannert, Karen; Rohde, Sarah; Berlin, Peggy; Reiner, Johannes; Wiese, Mats; Doller, Julia; Lerch, Markus M.; Aghdassi, Ali A.; Meyer, Fatuma; Valentini, Luzia; Agrifoglio, Ottavia; et al.
Abstract: Muscle wasting represents a constant pathological feature of common chronic gastrointestinal diseases, including liver cirrhosis (LC), inflammatory bowel diseases (IBD), chronic pancreatitis (CP) and pancreatic cancer (PC), and is associated with increased morbidity and mortality. Recent clinical and experimental studies point to the existence of a gut‐skeletal muscle axis that is constituted by specific gut‐derived mediators which activate pro‐ and anti‐sarcopenic signalling pathways in skeletal muscle cells. A pathophysiological link between both organs is also provided by low‐grade systemic inflammation. Animal models of LC, IBD, CP and PC represent an important resource for mechanistic and preclinical studies on disease‐associated muscle wasting. They are also required to test and validate specific anti‐sarcopenic therapies prior to clinical application. In this article, we review frequently used rodent models of muscle wasting in the context of chronic gastrointestinal diseases, survey their specific advantages and limitations and discuss possibilities for further research activities in the field. We conclude that animal models of LC‐, IBD‐ and PC‐associated sarcopenia are an essential supplement to clinical studies because they may provide additional mechanistic insights and help to identify molecular targets for therapeutic interventions in humans.